SEBARAN LOGAM BERAT TERLARUT DAN TERENDAPKAN DI PERAIRAN TELUK JAKARTA - Anma Hari Kusuma; Tri Prartono; Agus S Atmadipoera; Taslim Arifin (Fakultas Perikanan dan Ilmu Kelautan, 2015)
Jakarta Bay is a crowded area with many activities so that a gathering place for pollutants from the land that is transported through the 13 rivers that flow in Jakarta. The purpose of this research is to explain the process and sources of heavy metal with to compare distribution profile heavy metal in water and sediment in Transitional Season I and Transitional Season II in the Jakarta Bay. The research heavy metal in water and sediment in Jakarta Bay was conducted in September 2014. Analysis of heavy metal in water and sediment use procedure (APHA 2012). The results showed hydro-oceanographic condition in the Jakarta Bay for current velocity range from 0.002-0.028 m/s to wards west and southwest, the wind speed range 4-17 knot blowing to the southwest and tidal tipe of single of riding the tide of 0,84 m. The temperature range 28.9-30.2 Â°C, salinity range 29.5-30.6 psu, acidity (pH) range 7.80-8.17 and suspended solid (TSS) range 25-68 mg/l. Heavy metals in water for Pb range 0.006-0.016 ppm, Cd range 0.001-0.003 ppm, Cu range from 0.001-0.005 ppm, Ni range 0.001-0.016 ppm and Zn range 0.003-0.097 ppm. Heavy metal in sediment for Pb range 24.86-59.32 ppm, Cd range 0.32-3.49 ppm, Cu range 11.42-67 ppm, Ni range 19.80-39.85 ppm and Zn range 26.14 to 241.01 ppm. Distribution of heavy metal in water and sediment to indicated the sources of heavy metal in the Jakarta Bay largely derived input material from the terrestrial.